Generic Substitution From Threat To Opportunity - Chudoba, Lubomír; Procházková, Markéta; Sýkora, Robert; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2012)
The objective of this thesis is to identify factors, which are influencing pharmacists` choice of a particular drug in a situation when generic substitution can be offered to a patient, and to analyse the relative importance of these factors for the pharmacists. This study investigates such behavioural patterns of pharmacists operating within chain of pharmacies called Alphega. The research consists of 2 consecutive parts; Firstly, qualitative inquiry through depth-in interviews has been carried out in order to identify variables, which may shape pharmacist's choice. And subsequently, quantitative investigation has been performed for the purpose of assessing importance of each variable. The results of the research have finally been used to evaluate the strategy of antibiotic Augmentin produced by company GlaxoSmithKline.
Vedoucí práce: Markéta Procházková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses